Cartel Damages and Cost Asymmetries - Petter Berg (Copenhagen Business School (CBS), 2012)
During the last ten years there has been a rigorous debate on how to improve anti-cartel enforcement in Europe. Introducing private enforcements systems, like in the US, was early in the process regarded as one of the most important steps for significant improvements. In contrast to public enforcement, private enforcement relies on adequate compensation to customers harmed by a cartel. But cartel damages are hard to calculate and the European Commission has therefore presented a draft guideline on how to quantify harm to assist courts and claimants. The focus in the guidance is on price effects, but cartels are also likely to cause other types of damage, such as efficiency effects. For example, a Swedish committee investigating cartels in the 1950's stated that ”A monopolist or a cartel can charge too high prices in relation to its costs. A cartel determines prices after the least efficient firm in the cartel, and hence protects it” (SOU 1951:27). This statement reflects an early awareness that pricing and efficiency effects from cartels are deeply related, and jointly determines the harm for consumers. This thesis aims at re-joining the discussion of cartel prices and efficiencies for the purpose of determining cartel damages. It will focus on the issue outlined above, i.e. cartel behaviour and the harm caused by cartels when a cartel consists of members that are not symmetric in costs. Cost asymmetries can be both exogenous and endogenous to cartel formation, but rather than discussing why asymmetries arise, I will in the four chapters focus on the effect the asymmetries have on cartel prices and hence consumer harm.
hdl:10398/8407
Keywords: 650